And Then There Were None: A Stall-Free Real-Time Garbage Collector for Reconfigurable Hardware. - Bacon, David F.; Cheng, Perry; Shukla, Sunil (Communications of the ACM, 2013)
The article discusses a garbage collector (GC), or automatic data storage management system, that is synthesized directly to hardware and is capable of collecting a heap of uniform objects completely concurrently. Background is presented on field-programmable gate arrays (FPGA), which are programmable logic devices including many discrete resources units enabled and connected depending on the user application. It describes the memory architecture and some alternatives, as well as the trade-offs. Miniheaps with one or two pointer fields and one or two data fields are highlighted.